THE IMPACT OF THE LAND RECLAMATION CENTER POINT OF INDONESIA ON FISHERMAN’S INCOME IN BONTORANNU VILLAGE, MARISO SUB-DISTRICT, SOUTH SULAWESI - Rahmat Rahmat; Ratu Anindya; Andi Naurah Zahra Azhar; Andi Alisha Filia Amadia; Khoiri; Darmawati (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2024)
Abstract. Land reclamation has become one of the alternatives to utilize marine areas for increasing land productivity. In the capital of South Sulawesi, Makassar City, the Center Point of Indonesia (CPI) project involves land reclamation as an effort by former governors of South Sulawesi in collaboration with private sectors to enhance the city's economic infrastructure. This research aims to analyze the impact of CPI land reclamation on fishermen's income in Bontorannu Village, Mariso Sub-district, Makassar City, and the efforts of fishermen in coping with reclamation that affects their income. The study employs field research using qualitative methods with data collection techniques such as observation, interviews, and documentation. The researcher proceeds with qualitative descriptive data analysis upon gathering all information and data. The findings indicate that there is a significant impact caused by the reclamation, namely a decline in income among fishermen in Bontorannu Village, Mariso Sub-district, due to difficulties in accessing fishing grounds, leading many fishermen to switch professions. Keywords: Impact, Reclamation, Fisherman, Income.